An evaluation of outpatient satisfaction based on the national standard questionnaire: a satisfaction survey conducted in a tertiary hospital in Shenyang, China - Xintong, Zhou; Tao, Xin; Shuying, Wang; Huq, K. A. T. M. Ehsanul; Huiying, Gao; Michiko, Moriyama (Frontiers in Public Health, 2024)
Background: Patient satisfaction survey serves as a pivotal tool in evaluating the quality of healthcare services. China’s nationwide standard patient satisfaction measurement tool was introduced in 2019. This study aims to assess the model fit of the national standard outpatient satisfaction questionnaire in a tertiary hospital and evaluate the outpatient’s satisfaction levels using this tool. Method: A cross-sectional survey using the national outpatient satisfaction questionnaire was conducted via message links to all hospital outpatients who registered between April and July 2022. The data collected underwent descriptive analysis, comparative analysis, and confirmatory factor analysis (CFA). Results: A total of 6,012 valid responses were received and analyzed during this period and 52.9% of the paticipants were female. The confirmatory factor analysis (CFA) model showed a good fit and identified doctor communication had the positive and environmental factor had the negative effects on outpatients satisfaction with standardized regression weights of 0.46 and 0.42, respectively. Despite the remarkably high satisfaction levels, patients’ recommendation for taking services was surpassed for overall evaluation and total satisfaction for this hospital. Conclusion: A disparity was identified between the expectations and real experiences of outpatients, leading to some extend of dissatisfaction. To enhance satisfaction levels, the hospital should improve the communication skills of all clinical staff, simplify the environment layout for first-time visitors, and manage patient overloads.